The Hungry Steppe : Famine, Violence, and the Making of Soviet Kazakhstan - Cameron, Sarah I., 1977- (Book collections on Project MUSE., 2018)
"The book brings the largely unknown story of the Kazakh famine of 1930-33 to light, using this case study to overturn several assumptions about violence, modernization, and nation-making under Stalin"--Provided by publisher.